Pandemic, public services and vulnerable workers in Portugal: an ambivalent relation? - Caleiras, Jorge (2022)
Citizens are the raison d'être of public services. The Covid-19 pandemic revealed its relevance, but also flaws in these services and the need to strengthen their role. This article analyses a set of vulnerable workers and their relational experiences with public services, in particular with the Employment, Social Security, Health, Education and Public Transportation services. Focusing on 53 interviews, conducted between 2019 and 2020, and on a set of 14 follow-up cases analysed during the first lockdown, the aim is to understand the interaction process and the development of perceptions regarding public services. The results, although ambivalent, revealed tensions between the needs and the criticism regarding their functioning, also pointing out to the revaluation of public services, particularly in a context of crisis, where they were called to play a crucial and irreplaceable role.